Discord in the family Sparidae (Teleostei): divergent phylogeographical patterns across the Atlantic-Mediterranean divide - Bargelloni, L. (2018)
The Strait of Gibraltar has been proposed to be the divide between two marine biogeographical regions, the Mediterranean Sea and the Northeast Atlantic. Intraspecific studies have shown, for several of the examined species, a reduction of gene flow between the two basins. The present study examines genetic variation at nuclear and mitochondrial loci in five marine teleost species belonging to the family Sparidae. Four samples for each species were analysed spanning the Northeast Atlantic and the Mediterranean. For all individuals 17 allozyme loci were scored and a combined single strand conformation polymorphism-sequencing approach was used to survey approximately 190 bp of the mitochondrial DNA (mtDNA) D-loop region. All five species share similar biological features. For three species, namely Lithognathus mormyrus, Spondyliosoma cantharus, and Dentex dentex, large mtDNA divergence was observed between Atlantic and Mediterranean samples. Little or no mtDNA differentiation was found in the other two species, Pagrus pagrus and Pagellus bogaraveo. Allozyme data revealed strong differentiation when comparing Atlantic and Mediterranean samples of L. mormyrus and D. dentex, moderate for P. pagrus, and no differentiation for P. bogaraveo and S. cantharus. These results provide evidence for a sharp phylogeographical break (sensu Avise) between the Atlantic and the Mediterranean for two (or possibly three) sparid species of the five investigated. At the same time, the obtained results for the other two species raise the question on which ecological/historical factors might have caused the observed discrepancy in the geographical distribution of genetic variation among otherwise biologically similar species.